Financial Cooperatives in Advancing Financial Inclusion: A Comparative Analysis of Tanzania and Indonesia - Ahmed, Issa G. (PT. Riset Press International, 2025)
Financial cooperatives are steadily being identified as the necessary means to expand access to low-cost financial services, especially in emerging economies where high proportions of the population are not yet included in formal financial systems. This article is a comparative analysis of financial cooperatives in Tanzania and Indonesia, with emphasis on the role in promoting financial inclusion, financial regulations, and new digital developments. Based on secondary analysis of national surveys, government reports, and academic research, the analysis identifies the achievements and current issues of both countries. Savings and Credit Cooperative Societies (SACCOS), a component of the tiered microfinance system in the Bank of Tanzania, have been brought into the picture, and formal financial inclusion has increased to 76% in 2023 (FinScope Tanzania, 2023). Cooperatives in Indonesia include Koperasi Simpan Pinjam (KSP) and Islamic Baitul Maal wat Tamwil (BMT), and financial inclusion is 80.51% in 2025 (OJK, 2025). The results show that Tanzania has been improving in agricultural financing and mobile-money integration and Indonesia in sharia-compliant cooperative financing and in support of SMEs. The comparative analysis implies the possibility of cross-learning: Tanzania may learn models of the Indonesian sharia and literacy programs, whereas Indonesia may learn the experience of the Tanzanian tiered regulatory system and the practice of agrifinance. The analysis concludes that the two systems continue to need professionalization, integration into the digital realm, and better governance to spur inclusive growth.